Technology enhanced learning and cognition - Dror, Itiel E. (Benjamins current topics ;, 2011)
The use of technology in learning has increased dramatically. Training and education is now utilizing and almost integrated with the World Wide Web, podcasts, mobile and distant learning, interactive videos, serious games, and a whole range of e-learning. However, has such technology enhanced learning been effective? And how can it better serve training and education?E-learning must be 'brain friendly', so it optimizes learning to the cognitive architecture of the learners. If technology enhanced learning promotes the formation of effective mental representations and works with the human cogni.